2022
DOI: 10.1002/ctm2.743
|View full text |Cite
|
Sign up to set email alerts
|

Targeting DCLK1 overcomes 5‐fluorouracil resistance in colorectal cancer through inhibiting CCAR1/β‐catenin pathway‐mediated cancer stemness

Abstract: Background To date, 5‐fluorouracil‐based chemotherapy is very important for locally advanced or metastatic colorectal cancer (CRC). However, chemotherapy resistance results in tumor recurrence and metastasis, which is a major obstacle for treatment of CRC. Methods In the current research, we establish 5‐fluorouracil resistant cell lines and explore the potential targets associated with 5‐fluorouracil resistance in CRC. Moreover, we perform clinical specimen research, in vitro and in vivo experiments and molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…In HCC, the interaction of CCAR1 with β-catenin induces cancer stem cell enrichment via activation of Wnt target genes [61]. The same mechanism is utilized in 5-fluorouracil resistant colorectal cancer models as CCAR1 associates with β-catenin and triggers a stemness-like phenotype by inducing Myc among others [62]. Knockdown of SH3PXD2B reduces invadopodia formation and subsequently lung metastasis in in vivo models [63].…”
Section: Discussionmentioning
confidence: 99%
“…In HCC, the interaction of CCAR1 with β-catenin induces cancer stem cell enrichment via activation of Wnt target genes [61]. The same mechanism is utilized in 5-fluorouracil resistant colorectal cancer models as CCAR1 associates with β-catenin and triggers a stemness-like phenotype by inducing Myc among others [62]. Knockdown of SH3PXD2B reduces invadopodia formation and subsequently lung metastasis in in vivo models [63].…”
Section: Discussionmentioning
confidence: 99%
“…UVRAG expression in HCT116 cells was predominantly lower than that in HCT116-self cells (Figure 3E). Doublecortin-like kinase 1 (DCLK) was reported as a marker of CSCs, involved in resistance to 5-Fu and radiotherapy [15,16]. Therefore, UVRAG expression in DCLK+ HCT116 and DCLK-HCT116 cells was detected, and it was found that DCLK+ HCT116 cells showed a higher UVRAG expression (Figure 3F), suggesting that UVRAG might be associated with CRC stem cells.…”
Section: Uvrag Contributed To Resistance To Radiotherapy and Chemothe...mentioning
confidence: 96%
“…Wnt/β-catenin induced CRC treatment resistance has been attributed to mainly three aspects: highly metastatic CSCs, regulation of non-coding RNA, and TME regulation ( Zhao et al, 2022 ). For instance, doublecortin-like kinase 1 (DCLK1), a cancer stem cell marker could confer the 5-FU resistance in CRC via the aberrant activation of Wnt/β-catenin signaling ( Wang et al, 2022a ). Cetuximab resistance was found to be related to the upregulation of miR-199b-3p via the activation of the Wnt/β-catenin pathway ( Han et al, 2022 ).…”
Section: Mechanisms Of Treatment Resistance In Mcrcmentioning
confidence: 99%